Outcomes After a Single Ovarian Stimulation Cycle in Women of Advanced Reproductive Age: A Retrospective Analysis - Liu, Mengdi; Zhao, Xusheng; Peng, Yuanyuan; Zheng, Jiahua; Guo, Kaixuan; Fan, Yanli; Jiang, Lei; Yang, Aimin; Cui, Na; Hao, Guimin; Wang, Wei (Frontiers in Endocrinology, 2022)
Objectives Previous studies showed that age is the most important factor that determines the outcome after embryo transfer (ET), with either in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI), regardless whether fresh or frozen cycles. The average cumulative live birth rate (CLBR) following a single ovarian stimulation cycle in women of advanced reproductive age (≥38 years of age) has been reported to be 22.6–34.1%. The purpose of this study is to compare the CLBR after a single ovarian stimulation cycle in women of different advanced reproductive age bracket (38/39, 40/41, 42/43 years of age or older), and to explore the factors (e.g., age, type of infertility, body mass index (BMI), ovarian stimulation protocols) associated with CLBR. Methods This retrospective analysis included all women of advanced reproductive age (38 years or older) undergoing IVF or ICSI at authors’ institute during a period from January 1, 2016 to December 31, 2018. The study protocol was approved by the Ethics Committee of the Second Hospital of Hebei Medical University (No. 2021-P045). Subjects with underlying diseases were excluded from analysis. The last follow-up was conducted in December 2020, with minimal 2-year follow-up. Results The final analysis included 826 women (40.00 ± 2.10 years of age at the time of ovarian stimulation; n = 633 and 193 for IVF-ET and ICSI-ET, respectively). The number of women in each age bracket was: 424 for 38/39 y, 226 for 40/41 y, 118 for 42/43 y, and 58 for ≥44 y. The number of transferable embryos was 2 (interquartile range: 2,4) for 38/39 y, 2 (2,3) for 40/41 y, 2 (2,3) for 42/43 y, and 2 (1.75,3) for ≥44 y. The rate of fresh embryo transfer was comparable (62.03–72.58%) among the 4 age brackets. The average CLBR following a single cycle was 26.27% in the overall study population, 32.31% for 38/39 y, 26.99% for 40/41 y, 14.4% for 42/43 y, and 3.44% for ≥44 y (P <0.001). In multivariate regression, CLBR was independently associated with younger age (OR for each year: 1.538, 95%CI: 1.193, 1.984) and higher number of transferable embryos (OR for each embryo: 1.495, 95%CI: 1.297, 1.722). CLBR differed significantly in the 38/39 group (P = 0.014), with higher rate in women receiving the Gonadotropin-releasing hormone agonist (GnRH-a) long or GnRH-a ultra-long protocols. Conclusions Forty-two years of age seemed to be a critical cutoff to achieve reasonable level of CLBR after a single ovarian stimulation cycle in women of advanced reproductive age.